Influence of biostimulants on growth, yield and benefits of soybean in Northern transition zone of Karnataka: Influence of biostimulants on growth, yield and benefits of soybean in Northern transition zone of Karnataka - G AISHWARYA; G SOMANAGOUDA; R CHANNAKESHAVA; J A HOSMATH; HARSHIY BANU (Journal of Oilseeds Research, 2023)
Field experiment was executed on “Influence of biostimulants on growth, yield and economics of soybean in Northern transition zone of Karnataka. Eleven treatments consists of foliar application at various concentration of Biostimulants (CropMax and Biozyme) at flowering and pod formation stage. Significantly higher dry matter accumulation (80.68 g/plant), seed yield (2,693 kg/ha), net returns (Rs. 1,03,702/ha) and BC ratio (3.4) were recorded with the foliar application of CropMax @ 700 ml/ha at flowering followed by Biozyme @ 625 ml/ha at pod formation stage.